Land, Power and Prestige Bronze Age Field Systems in Southern England - Yates, David T. (Historic England, 2007)
A major phase of economic expansion occurred in southern England during the second and early first millennium BC, accompanied by a fundamental shift in regional power and wealth towards the eastern lowlands. This book offers a synthesis of available data on Bronze Age lowland field systems in England, including a gazetteer of sites. The research demonstrates the importance of large-scale animal husbandry in the mixed farming regimes as evidenced in the design of the field systems which incorporate droveways, stock proof fencing, watering holes, cow pens, sheep races and gateways for stockhandling. It is argued that the field systems represented a form of conspicuous production, an "intensification" of agrarian endeavour or a statement of intent, to be understood in relation to the maintenance, display and promotion of hierarchical social systems involved in exchange with their counterparts across the English Channel.